The new campaign finance sourcebook - Corrado, Anthony, 1957- (Brookings Institution Press, 2005)
"Comprehensive exposition of federal campaign finance law and administration following the enactment, consitutional defense, and implementation of the 2002 Bipartisan Campaign Finance Reform Act (McCain-Feingold)"--Provided by publisher